Approximation to the Consumption of Healthcare Resources and the Economic Cost of SARS-CoV-2 Patient Management: A Retrospective Study - Calderón-Moreno, Jesús; Juárez-Vela, Raúl; Delgado-Rodríguez, María Jesús; Quintana-Díaz, Manuel; Magallón-Botaya, Rosa; Olivan-Blázquez, Bárbara; Cobos-Rincón, Ana; Santolalla-Arnedo, Iván; Ramírez-Torres, Carmen Amaia; Gea-Caballero, Vicente; Andrés-Esteban, Eva María (Frontiers in Public Health, 2022)
Spain has become one of the countries most affected by coronavirus disease 2019 (COVID-19), with the highest testing rates, and one of the worst-performing countries in the fight against the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic. There are no studies related to the consumption of health resources and the economic cost of the SARS-CoV-2 virus. We present a retrospective analysis of 9,811 (Primary Care and Hospital) patients which aimed to estimate public health expenditure by the consumption of health resources due to COVID-19. According to the results, the gender distribution of patients has a similar rate in both groups, with slightly higher rates in women. Similarly, age is the same in both groups, with a median of 62 years in the case of hospitalizations and 61 years in the case of primary care; using a weighted average of these rates and costs, we can estimate that the average cost of care per patient infected with the SARS-CoV-2 virus, regardless of the course is €2373.24. We conclude that a patient with COVID-19 without hospitalization costs €729.79, while the expenses of a hospitalized patient are between €4294.36 and €14440.68, if there is ICU admission.